Screening of polyketide genes from Brazilian Atlantic Forest soil (Universitas Scientiarum, 2017)
Soil is a large source of microorganisms with potential to produce bioactive compounds. Since most of them cannot be cultured, metagenomics has become a useful tool in order to evaluate this potential. The aim of this study was to screen biosynthetic polyketide genes (PKS) present in a metagenomic library constructed from a soil sample isolated from the Brazilian Atlantic Forest. The library comprises 5000 clones with DNA inserts between 40 and 50 Kb. The characterization of the biosynthetic gene clusters of these molecules is a promising alternative to elucidate the biotechnological potential of bioactive compounds in microbial communities. The PKS genes were screened using degenerated primers. The positive clones for PKS systems were isolated, and their nucleotide sequences analysed with bioinformatics tools. The screening yielded two positive clones for PKS II genes. Furthermore, variations in the sequences of the PKS II genes from the metagenomic library were observed when compared with sequences of ketosynthases’ databases. With these findings we gain insight into the possible relation between new biosynthetic genes and the production of new secondary metabolites.